Effect of incorporation of POSS compounds and phosphorous hardeners on thermal and fire resistance of nanofilled aeronautic resins1. Issue 15 (25th February 2015) - Raimondo, M.; Russo, S.; Guadagno, L.; Longo, P.; Chirico, S.; Mariconda, A.; Bonnaud, L.; Murariu, O.; Dubois, Ph.
<x xml:space="preserve">Abstract</x> The aim of this work is the identification of the best strategy for improving thermal, fire resistance and electrical conductivity of an epoxy resin for aeronautic applications.